Estudio virológico de casos mortales de poliomelitis paralítica II. Aislamiento de Poliovirus de Líquido Cefalorraquídeo (post Mortem) - Célis G., Eduardo (1969)
6 samples of cerebrospinal fluid was subjected to virological study post-mortem, from 6 cases of Paralytic Poliomiellitis occurred in the Children's Hospital (Lima), having obtained the following results: In case 1, poliovirus type II was isolated; in case 3, poliovirus type III asisló; in case 4, Poliovirus Type I, and the cases 2, 5 and 6 were negative was isolated.